2019
DOI: 10.1177/2396941519896736
|View full text |Cite
|
Sign up to set email alerts
|

Fiction or non-fiction: Parent-reported book preferences of their preschoolers with autism spectrum disorder

Abstract: Background and aims: Children's early interactions with books are important for fostering development of oral language and emergent literacy skills. It is not known whether children diagnosed with autism spectrum disorder show different preferences for text types in the home environment prior to school entry. The current study aimed to: (i) investigate parent-reports of the favourite books of their children with autism spectrum disorder compared to typically developing children and (ii) identify whether there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, developmental evidence suggests that exposing children to fiction books is a significant predictor of better ToM ability, whereas non‐fiction was a negative predictor (Mar et al, 2006). However, despite the assumption that children with ASC prefer non‐fiction books over fiction books, no difference in book preferences could be observed (Armstrong et al, 2019; Davidson & Ellis Weismer, 2018). As the study was correlational, the directionality of the relationship cannot be determined for sure, however, no difference between the ASC group and the non‐ASC group could be identified in reading frequency, hereby suggesting that reduced mentalizing ability does not automatically reflect a dislike for fiction consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, developmental evidence suggests that exposing children to fiction books is a significant predictor of better ToM ability, whereas non‐fiction was a negative predictor (Mar et al, 2006). However, despite the assumption that children with ASC prefer non‐fiction books over fiction books, no difference in book preferences could be observed (Armstrong et al, 2019; Davidson & Ellis Weismer, 2018). As the study was correlational, the directionality of the relationship cannot be determined for sure, however, no difference between the ASC group and the non‐ASC group could be identified in reading frequency, hereby suggesting that reduced mentalizing ability does not automatically reflect a dislike for fiction consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it has been assumed that autistic individuals would prefer the systematic nature of factual non-fiction (Baron-Cohen, 2009 ; Barnes, 2012 ). However, recent findings have contradicted dominant assumptions, showing instead that autistic individuals across age groups do engage with fiction and literary non-fiction (Barnes, 2012 ; Davidson and Ellis Weismer, 2018 ; Armstrong et al, 2019 ; Chapple et al, 2021a ). Additionally, findings show that when asked about their experiences of reading, autistic participants report examples of felt empathy for fictional characters and book authors themselves (Chapple et al, 2021a ).…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, it has been suggested that autistic people may prefer non-fiction ( Baron-Cohen, 2008 ; Barnes, 2012 ). Although research has demonstrated that autistic people do enjoy and engage with fiction ( Barnes, 2012 ; Davidson and Ellis Weismer, 2018 ; Armstrong et al, 2019 ; Chapple et al, 2021b ), qualitative research has highlighted that autistic people can find emotional value in reading biographical non-fiction and factual non-fiction that relates to specialized interests ( Chapple et al, 2021b ). Arguably, serious literature contains autobiographical elements within it, due to the author’s own personal involvement in the fictional narrative ( Zunshine, 2011 ; McCartney, 2021 ).…”
Section: Introductionmentioning
confidence: 99%